2014
DOI: 10.1016/j.jaac.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of American and English Hospital Discharge Rates for Pediatric Bipolar Disorder, 2000 to 2010

Abstract: Objective Controversy exists over the diagnosis and prevalence of pediatric bipolar disorder (PBD). Although several small surveys suggest that the rate of the PBD diagnosis in clinical settings is higher in the United States than in other countries, no comprehensive cross-national comparisons of clinical practice have been performed. Here, we used longitudinal national datasets from 2000 to 2010 to compare US and English hospital discharge rates for PBD in patients aged 1 to 19 years. Method We used the Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…In line with this, recent work (James et al, 2014) found the rates of admission for BP to be very low in the England until after age 19, consistent with a possible under-diagnosis or late diagnosis. Further limitations of this study include the fact that diagnoses were not standardised, relying instead upon routine clinical assessments and recording at each hospital.…”
Section: Limitationssupporting
confidence: 60%
“…In line with this, recent work (James et al, 2014) found the rates of admission for BP to be very low in the England until after age 19, consistent with a possible under-diagnosis or late diagnosis. Further limitations of this study include the fact that diagnoses were not standardised, relying instead upon routine clinical assessments and recording at each hospital.…”
Section: Limitationssupporting
confidence: 60%
“…2010). The latter is supported by the already increasing use of psychotropic medication in CYP in the United States (Olfson et al 2002) Europe (Steinhausen & Bisgaard, 2014) and the UK (Middleton et al 2001; Rani et al 2008; Lockhart & Guthrie, 2011; John et al 2015) but may be more of an issue for the United States due to differing diagnostic practices (James et al 2014). Nonetheless mental health and well-being are of increasing public health importance worldwide, with depression estimated to be the leading cause of disease burden by 2030 (WHO, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas prevalence of BD-I and -II in youth in the general population is not different between US and non-US countries (Van Meter et al, 2011), clinical studies have shown an increase in the “administrative” prevalence of outpatient visits and hospital admission rates of BD in youth in the United States (US) as compared to most other countries (Holtmann et al, 2010; James et al, 2014; Kozloff et al, 2010; Soutullo et al, 2005). Comparisons between US and European adult patients with BD have also shown higher prevalence, younger age of onset, more severe illnesses, and increased parental history of BD in the US (Bellivier et al, 2011; Post et al, 2008, 2014a, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…parental- or offspring characteristics), methodological (e.g. recruitment method, assessment instruments, information source, age at assessment) or cultural factors and differences (Carlson and Klein, 2014; Duffy et al, 2011; James et al, 2014; Merikangas et al, 2011; Soutullo et al, 2005). Thus far, cross-national variability in psychopathology among bipolar offspring has not been well studied.…”
Section: Introductionmentioning
confidence: 99%